Exercise Physiology - Ferraz, Ricardo; Neiva, Henrique; Marinho, Daniel A.; Teixeira, José E.; Forte, Pedro; Branquinho, Luís (IntechOpen, 2022)
Exercise physiology is one of the most researched sports sciences, with practical implications for health, well-being and sports performance. This book brings together emerging research in this area, presenting the main findings and criticisms, as well as considering the future of exercise physiology.